Force generation of jumpers on the in-run area of three hill sizes - Sasaki, T.; Tsunoda, K.; Hoshino, H. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Forces from different sources act on the ski jumper during the in-run. More specifically, the in-run is constructed to be similar on different ski jumping hill sizes. Jump motion is performed on the take-off platform of the in-run. Basically, forces the jumper obtains from the in-run should be similar in any different size of jumping hill. The purpose of this study is to reveal the forces generated on the in-run of three different sizes of jumping hills.